The impact of the COVID-19 pandemic on police recorded domestic abuse: Empirical evidence from seven English police forces - Hohl, Katrin (Criminology & criminal justice, 2025)
The COVID-19 pandemic and associated lockdowns have provided an unprecedented opportunity to study how such situational factors affect police recorded domestic abuse. This article presents findings from a large, representative study of the effect of the introduction and lifting of lockdowns on the volume and nature of domestic abuse recorded by seven English police forces within the first 12 months of the pandemic. The results suggest that lockdowns and the pandemic context did not create the domestic abuse crisis, and that the crisis does not go away when lockdown restrictions lift. Lockdowns interact with and amplify underlying patterns of domestic abuse. Notable differences between police forces suggest that local contexts and local police force practices play a role, with implications beyond pandemic contexts.